The action of bacteria on foods - Rigg, Eva T. (My University, 1902)
Introduction: The subject of Bacteriology is one which has but recently been brought before the public. The discoveries which have been made along this line in the last fifty years have been marvelous and there is no doubt but what the work is just fairly begun. There is a wide field open for investigation by scientists. The necessity of this investigation is obvious enough when we consider the close relation which bacteria bear to human life or indeed to any kind of life, either animal or vegetable. A knowledge of bacteria is necessary to every individual, for we meet them everywhere in life, they are omnipresent. The earth, the water and the air about us are supplied with them. They are very social and dwell with us in our houses, sit with us at our tables, cling to our clothing, and take up their abode in our food and drink. They are our greatest friends as without them it would be impossible to live. They are also our greatest enemies, for they are the initiative of the greater part of all the diseases and death in the world.
Citation: Rigg, Eva T. The action of bacteria on foods. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Bacteria; Bacteriology; Biology; Theses; Manuscripts (documents)